Innovative Primary Frequency Control in Low-Inertia Power Systems Based on Wide-Area Rocof Sharing - Chavez-Orostica, H (Institution of Engineering and Technology, 2020)
Future plans for integration of large non-synchronous generation and the expansion of the power system in the Nordic countries are a concern to transmission system operators due to the common interconnections and electricity exchanges among these operative areas. The expected reduction in the inertia anticipates an alteration of the frequency response, provoking a high Rate of Change of Frequency (RoCoF) slopes that can jeopardise the security of the interconnected systems. Since power generation in the Nordic countries such as Sweden, Finland and Norway is hydro-dominated, here, the authors propose a novel solution to tackle this problem including wide area measurements to monitor and share the RoCoF in remote areas with lower inertia to enhance their primary frequency control. To demonstrate the effectiveness of the proposed solution, first a test benchmark control with optimised parameters is developed and later compared against the proposed method. Additionally, since the proposed solution is based on measurements from remote locations in order to guarantee the stability of the system the impact of delays in the communication channels is also included in the problem formulation. © 2020 IET Energy Systems Integration. All rights reserved.